2022
DOI: 10.1002/ejsp.2840
|View full text |Cite
|
Sign up to set email alerts
|

On the use of gender categories and emotion categories in threat‐based person impressions

Abstract: People often form impressions of others in contexts where both relatively static demographic cues (e.g., age, race, gender) and situationally flexible, dynamic cues (e.g., emotion expressions) are available. We examined whether and how attending to gender (male, female) versus emotion expression (neutral, smiling) affects threat-based person impressions. In three experiments, we heightened the salience of either gender categories or emotion categories in a sequential priming task. Category salience consistentl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 51 publications
(98 reference statements)
0
1
0
Order By: Relevance
“…The prime faces were the immigrant and citizen individual images from the image-generation experiment, as well as a featureless outline of a human head that is commonly used in this task. For ease of presentation, and following other SMT research [ 34 , 61 ], we did not include the featureless prime in the analyses reported below. Indeed, it is typical for the featureless prime to elicit negativity [ 62 , 63 ].…”
Section: Methodsmentioning
confidence: 99%
“…The prime faces were the immigrant and citizen individual images from the image-generation experiment, as well as a featureless outline of a human head that is commonly used in this task. For ease of presentation, and following other SMT research [ 34 , 61 ], we did not include the featureless prime in the analyses reported below. Indeed, it is typical for the featureless prime to elicit negativity [ 62 , 63 ].…”
Section: Methodsmentioning
confidence: 99%